2016
DOI: 10.1016/j.micromeso.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic nanohybrids of novolac phenolic resin and carbon nanotube: High carbon yields by using carbon nanotube aerogel and resin incorporation into aerogel network

Abstract: CNTCOOH was prepared from oxidation of carbon nanotube. Subsequently, CNTSi was prepared by grafting (3-glycidyloxypropyl) trimethoxysilane (GPTES) to the surface of CNTCOOH by a ring opening reaction of epoxy groups. Then, CNTA was obtained by formation of silicon oxide network between CNTSi and tetraethyl orthosilicate (TEOS). Finally, CNTA was used as an additive in novolac resin matrix to yield RCNTA composites with high carbon yield values. Additionally, modification of novolac resin by GPTES gives MR wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…By the oxidation, modification, and hybrid network formation, the I D /I G value is increased which indicates that modification of CNTOH by HDBTMSPU and also sol-gel process have been carried out successfully [50]. The peaks at 532 and 1072 cm -1 are related to Si-O network [29,30]. Additionally, the peaks appeared at 731 and 941 cm -1 are related to Si-C group [58].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…By the oxidation, modification, and hybrid network formation, the I D /I G value is increased which indicates that modification of CNTOH by HDBTMSPU and also sol-gel process have been carried out successfully [50]. The peaks at 532 and 1072 cm -1 are related to Si-O network [29,30]. Additionally, the peaks appeared at 731 and 941 cm -1 are related to Si-C group [58].…”
Section: Resultsmentioning
confidence: 93%
“…Accordingly, CNTX shows pore size in the range of 2-100 nm. However, the size of a large number of pores is 2-10 nm, which shows that CNTX can be categorized in mesoporous materials [29,30]. Considering cylindrical pore geometry, pore diameters can be calculated by D = 4V p /S BET , where D is the average pore diameter and V p is the pore volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These organic-inorganic hybrid materials can be prepared by co-condensation of modified polymers with metal alkoxides and formation of covalent bonding between the organic and inorganic components [16]. In sol-gel methods, hydrolysable alkoxysilanes are commonly used as coupling agents and pH, alkoxide type, water amount, temperature, and drying methods are important factors controlling the hydrolysis and condensation reactions [17][18][19][20]. Uniform distribution of silica/siloxane domains within a polymer matrix in co-condensation process may result in higher thermal and mechanical properties in such hybrid materials.…”
mentioning
confidence: 99%
“…Additionally, char residue is increased by 16.93% by loading only 1 wt% of functionalized-GO in silane-modified epoxy resin matrix. In addition, modified CNT and novolac resin with alkoxysilane modifiers was incorporated into silica/siloxane network through the solgel method using tetraethyl orthosilicate (TEOS) by Noparvar-Qarebagh et al [18]. They showed that 11.94% increase of char yield was achieved by incorporation of functionalized-CNT in silane-modified novolac resin matrix.…”
mentioning
confidence: 99%